Keynesian Macroeconomic Policy: Theoretical Analysis and Empirical Evidence - Arestis, Philip; Ferrari Filho, Fernando; Bittes Terra, Fábio Henrique (Panoeconomicus, 2018)
Investment depends on subjective factors, such as expectations, conventions, and confident animal spirits. In a context of economic instability and crises, economic policy is the main source to support entrepreneurs’ expectations and investment. In this sense, macroeconomic policies are capable of affecting effective demand and building a good institutional environment, which is essential to keep the entrepreneurs’ expectations confident and promote their animal spirits. Given these propositions, this contribution has two objectives. The first is to develop a Keynesian type of macroeconomic policy able to stimulate investment and effective demand, and, as a result, mitigate unemployment. The idea is to offer alternative macroeconomic policy prescriptions in relation to the New Consensus Macroeconomics one. This proposal aims to establish the role, according to the Post Keynesian view, the logic of operation of each policy, and the proper coordination among these Keynesian macroeconomic policies. The second objective is to present, briefly, relevant empirical evidence of the Post Keynesian macroeconomic policies.Key words: Keynes, Economic policy, Fiscal policy, Monetary policy, Exchange rate policy. JEL: E12, E60, E62. Investicije zavise od subjektivnih faktora, kao što su očekivanja, konvencije i pouzdani životinjski duh. U kontekstu ekonomske nestabilnosti i krize, ekonomska politika je glavni izvor podrške očekivanjima i investicijama preduzetnika. U tom smislu, makroekonomske politike mogu da utiču na efektivnu potražnju i izgradnju dobrog institucionalnog okruženja, što je od suštinske važnosti da se očekivanja preduzetnika osiguraju i da promovišu njihov životinjski duh. Imajući u vidu ove predloge, ovaj doprinos ima dva cilja. Prvi je da razvije Kejnzijansku vrstu makroekonomske politike koja može stimulisati investicije i efektivnu potražnju, a kao rezultat toga ublažiti nezaposlenost. Ideja je ponuditi alternativne preporuke o makroekonomskoj politici u odnosu na novi makroekonomski konsenzus. Takav predlog ima za cilj da utvrdi ulogu, prema Post Kejnzijanskom pogledu, logiku rada svake politike i odgovarajuću koordinaciju između ovih Kejnzijanskih makroekonomskih politika. Drugi cilj je da predstavi, ukratko, relevantne empirijske dokaze ove post Kejnzijanske makroekonomske politike.Ključne reči: Kejnz, ekonomska politika, fiskalna politika, monetarna politika, politika deviznog kursa.